INNOVATIVE PSYCHOLOGICAL APPROACHES TO ENSURING FAMILY STRENGTH. INFLUENCE OF FAMILY ENVIRONMENT ON THE FORMATION OF TALENT IN SCHOOL STUDENTS. - Abdullayeva , Zuhro Ismoilovna (Innovative Development in Educational Activities, 2024)
In this article, the family plays an important role of the external environment in the development of talent in schoolchildren. Family is a part of society, in which a new person is born, it is the elementary school of life for a small social group. Parents, as the child’s first teacher and educator, must first be psychologically prepared, talent is a specific form of abilities that ensure successful performance.